2008
DOI: 10.1002/pssb.200879560
|View full text |Cite
|
Sign up to set email alerts
|

A detailed comparison of CVD grown and precursor based DWCNTs

Abstract: Double‐wall carbon nanotubes (DWCNTs) grown directly via a CVD method and DWCNTs produced by annealing C60 and ferrocene filled single‐wall carbon nanotubes were studied with X‐ray diffraction (XRD) and Raman spectroscopy. The samples showed the typical XRD patterns of hexagonally bundled tubes. The frequencies and linewidths of the inner tube radial breathing modes (RBMs) were (with in experimental precision) equal in all three samples only the intensities differed. Finally, all samples showed the typical clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…A good example is the (6,4)@(12,8) nanotube, where we predict a RBM frequency of 346.5 cm −1 as opposed to 339 cm −1 from previous works. 21,44 Further examples that we assigned differently are (6,4) @(11,10), (6,4)@(13,8), and (6,4)@(14,8). In the weakcoupling regime both models seem to deliver similar results; however, the underlying model of Pfeiffer et al 21,28 is not compatible with the optical energy shifts.…”
Section: ■ Resultsmentioning
confidence: 99%
“…A good example is the (6,4)@(12,8) nanotube, where we predict a RBM frequency of 346.5 cm −1 as opposed to 339 cm −1 from previous works. 21,44 Further examples that we assigned differently are (6,4) @(11,10), (6,4)@(13,8), and (6,4)@(14,8). In the weakcoupling regime both models seem to deliver similar results; however, the underlying model of Pfeiffer et al 21,28 is not compatible with the optical energy shifts.…”
Section: ■ Resultsmentioning
confidence: 99%
“…4 According to Bandow et al, under prolonged heat treatment the initial diameters of the inner tubes can increase in order to adjust the wall-to-wall (WtW) distances and minimize the energy of the system. 4 Also, by using highresolution Raman spectroscopy, Pfeiffer et al [5][6][7][8] and Kuzmany et al, 9 observed that the inner tubes of C 60 -DWNTs can be contained inside outer tubes with different diameters where smaller WtW distances increase the inter-tube interaction and upshift the radial breathing mode (RBM) of the inner tubes. CVD-DWNTs and C 60 -DWNTs have been shown to have different optical properties that are believed to originate from differences in the WtW distances and the degree of crystallinity of the inner tubes.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The CVD-DWNTs and C 60 -DWNTs have been reported to have some differences in their electronic and optical properties due to differences in the crystallinity of the resulting inner tubes and in the characteristic distance between the inner and outer tubes. 4 For instance, C 60 -DWNTs have been observed to have smaller average wall to wall distances ͑defined as the distance between the inner and outer walls of the DWNT͒ than CVD-DWNTs for DWNTs with similar inner diameters. Also, the photoluminescence ͑PL͒ emission from the inner tubes of DWNTs appears to be highly dependent on sample fabrication and pu-rity because both high and low intensity PL signals from the inner tubes of DWNTs have been reported for CVD-DWNTs 5 and C 60 -DWNTs, 6 respectively.…”
Section: Introductionmentioning
confidence: 99%